2020
DOI: 10.1002/he.20364
|View full text |Cite
|
Sign up to set email alerts
|

Not All Regional Public Universities Strive for Prestige: Examining and Strengthening Mission‐Centeredness Within a Vital Sector

Abstract: A dominant narrative exists that all regional public universities (RPUs) are striving for prestige and, if given the chance, would readily abandon their missions of facilitating educational access for marginalized students and increase admissions selectivity to privilege elite students. As a result of this dominant narrative, RPUs are largely depicted as being unsure of and uncommitted to their missions. This chapter tests this dominant narrative by examining research and media reporting about the sector. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…An increase in the percentage of enrolled federal Pell Grant recipients (a proxy for low-income students) was associated with small upticks in enrollment share of URM students and in the diversity index score. This relationship is consistent with prior research highlighting mission-driven PMIs that serve local, historically marginalized students (Fryar, 2015; McClure, 2018; Oprhan, 2018, 2020; Warshaw et al, 2020, 2021). We also found that an increase in international student enrollment was associated with a decrease in URM enrollment share and an increase in the diversity index score.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…An increase in the percentage of enrolled federal Pell Grant recipients (a proxy for low-income students) was associated with small upticks in enrollment share of URM students and in the diversity index score. This relationship is consistent with prior research highlighting mission-driven PMIs that serve local, historically marginalized students (Fryar, 2015; McClure, 2018; Oprhan, 2018, 2020; Warshaw et al, 2020, 2021). We also found that an increase in international student enrollment was associated with a decrease in URM enrollment share and an increase in the diversity index score.…”
Section: Discussionsupporting
confidence: 89%
“…We expect that an increase in graduate enrollment and in research spending will, due to connections to tuition price, each be associated with a decrease in racial diversity at PMIs. But PMIs’ expansion of graduate education and research could be mission-centered when their initiatives align with community-based needs (Fryar, 2015; Henderson, 2007; Orphan, 2020; Zerquera, 2019). Such efforts may enhance or constrain racial diversity based on whether they serve access and equity or striving.…”
Section: Theoretical Framework and Propositionsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is not to say, however, that all contemporary HEIs have similar profiles, niches, and aspirations (Teichler 1988;Paradeise and Thoenig 2013). Orphan (2020) argues that many US regional colleges are less prone to prestige-seeking behaviour than what is often assumed in the higher education debate, cherishing the mission of regional access to postsecondary education. In the oldest and most prestigious institutions traditionally associated with a category of specialisation such as 'technical university', the social order that grants them status and incumbency may be treasured (Podolny 2010;Brankovic 2018).…”
Section: The Emergence Of a Global Hegemonic Categorymentioning
confidence: 99%